Educação Matemática e Inclusão Escolar: a construção de estratégias para uma aprendizagem significativa - Lanuti, José Eduardo de Oliveira Evangelista [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research was conducted under the Program of Graduate Studies in Education of the Faculty of Science and Technology - Universidade Estadual Paulista (FCT/UNESP) and inserted into the line of research Formative Processes and Practices in Education. It was also sponsored by Fundação de Amparo à Pesquisa do Estado São Paulo (FAPESP) - number 2012/17539-7. Considering the assumptions of a quality education for all, which is now the school inclusion parameter, supported by the current educational legislation, the teacher needs to develop methods and strategies that enhance meaningful learning and students' participation in the process of teaching and learning. School inclusion is associated with the school democratization process, thus the teachers' concern should focus on ―how‖ all students can learn. According to the assumptions of mathematics education, for the learning to be successful among students is significantly necessary to develop contextualized activities that make sense for them. Under these assumptions the general objective of this research was to identify which strategies used by teachers of Mathematics could promote greater participation of all students in the 6th grade of elementary school (participants in this study) and therefore enhance their experience in the classroom. This is a qualitative study of the intervention type. Two classes with 31 and 23 students took part in this research, and by reflecting upon their own practice the teacher considered which strategies would facilitate the learning process of such students and their participation in the lessons. The instruments used for data collection were the field journal and a camera for shooting the lessons...

A presente pesquisa de mestrado foi desenvolvida no âmbito do Programa de Pós-Graduação em Educação da Faculdade de Ciências e Tecnologia - Universidade Estadual Paulista (FCT/UNESP) e inserida na linha de pesquisa ―Práticas e Processos Formativos em Educação‖. Contou com financiamento da Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP) processo nº 2012/17539-7. Considerando os pressupostos de uma educação de qualidade para todos, que hoje é parâmetro da Inclusão Escolar, amparada pela legislação educacional vigente, o professor precisa desenvolver métodos e estratégias que favoreçam a aprendizagem significativa e a participação dos estudantes nos processos de ensinar e aprender. A inclusão escolar está relacionada ao processo de democratização da escola, e dessa forma a preocupação dos docentes deve estar voltada para o ―como‖ fazer para que todos aprendam. Conforme os pressupostos da Educação Matemática, para que todos aprendam significativamente é preciso desenvolver atividades contextualizadas que fazem sentido para os estudantes. Diante dessas premissas o objetivo geral desta pesquisa foi identificar quais as estratégias utilizadas pelo professor de Matemática da sala comum do ensino regular podem favorecer a participação e aprendizagem de todos os estudantes do 6º ano do Ensino Fundamental II, participantes desta pesquisa. Trata-se de uma pesquisa de cunho qualitativo do tipo intervenção...
Keywords: Educação; Educação - Matemática; Estratégias de aprendizagem; Inclusão em educação; Education